Evaluación de la calidad del servicio que brinda el área de emergencia del Centro de Salud Arnaldo Calderón del Cantón Tosagua. - Quijije Antón, Gema Carolina (2016)
The main goal of this research was to achieve public servants provide patients quality service with warmth, in such a way that at the end of the day will be held the success for the accomplished work, all this was possible by making use of methods which allowed us to deduce the source of the problems and their effects in this way could propose improvements allowing to provide a better health service to patients who came to the health unit; Likewise is applied them research to perform the Diagnostics in the place of them made through the observation and the application of the matrix SWOT / CAME which allowed know them weaknesses, threats, strengths and opportunities that existed in the same. For the analysis of the quality of the service was necessary use it matrix SERVQUAL tool indispensable for know it opinion of them people with regard to their expectations and perceptions of the service that received of part of them servers, for which is applied the survey to them patients that flocked to the area of emergency, then in the plan of improves is took as reference them results obtained which determined that not exists enough talent human specialized for meet the demand generated by them patients, this led to conclude that existed the need of apply continuously Diagnostics and actions that impact in it efficiency and efficiency of the service, coming so to socialize the proposed of the plan of improves to them officials of this dependence.